RUSSIAN BUSINESS DEVELOPMENT AT THE CURRENT STAGE OF RUSSIA-WESTERN ECONOMIC RELATIONSHIP - -, Nikiporets; Galina, Takigawa; Nikita, Kolpakov (Prosiding International conference on Information Technology and Business (ICITB), 2018)
The tensions in the relations between the Russian Federation and the West has been in the focus of modern global politics, especially in the last few years. Deteriorated diplomatic relations and mutual political and economic sanctions characterize the current situation. This disposition presents various issues of social and political character for Russian business development. The purpose of this article is to examine these issues and the measures the Russian government implements to address them. The authors analyzed official documents such as Economic Security Strategy until 2030, proceedings of Gaidar Forum and other top priority meetings, as well as the relevant sources and statistics. Several conclusions are made as a result of this research. The current political climate between the Russian Federation and the West affects the state of the Russian economy. Even though, the strategic vision for main challenges in Russian economy has been laid out, the perspective to resolve these challenges remain vague.Keywords: sanctions; Russian economy; economic growth; socio-political challenges; business-government relations